2012
DOI: 10.1093/cid/cis909
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Colistin Dose and Microbiologic Outcomes in Patients With Multidrug-Resistant Gram-Negative Bacteremia

Abstract: Higher colistin dose independently predicted microbiological success, which may partially explain the similar association with 7-day mortality. However, higher colistin doses may also precipitate worsening renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
8
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 19 publications
2
70
8
3
Order By: Relevance
“…Subsequently, a study by Dalfino and colleagues (10) treated patients with a dosing schedule involving a loading dose of 9 million units (300 mg CBA) and a maintenance dose of 4.5 million units (150 mg CBA) every 12 h. This dosing regimen led to a clinical cure rate of 82%, which is the highest reported clinical cure rate reported for the use of systemic colistin for the treatment of multidrug-resistant Gramnegative infections (10). One of our previous studies similarly concluded that an increased dose of colistin independently predicts day 7 microbiologic success (2.9 versus 1.5 mg/kg/day; P ϭ 0.11) and is correlated with day 7 mortality (2.7 versus 1.5 mg/kg/ day; P ϭ 0.007) (12). The global cure rate of 40% in the current study is lower than that observed in previous studies, which may be attributable to our more stringent definition of global cure.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Subsequently, a study by Dalfino and colleagues (10) treated patients with a dosing schedule involving a loading dose of 9 million units (300 mg CBA) and a maintenance dose of 4.5 million units (150 mg CBA) every 12 h. This dosing regimen led to a clinical cure rate of 82%, which is the highest reported clinical cure rate reported for the use of systemic colistin for the treatment of multidrug-resistant Gramnegative infections (10). One of our previous studies similarly concluded that an increased dose of colistin independently predicts day 7 microbiologic success (2.9 versus 1.5 mg/kg/day; P ϭ 0.11) and is correlated with day 7 mortality (2.7 versus 1.5 mg/kg/ day; P ϭ 0.007) (12). The global cure rate of 40% in the current study is lower than that observed in previous studies, which may be attributable to our more stringent definition of global cure.…”
Section: Discussionmentioning
confidence: 79%
“…By using CART analysis, the current study was able to determine a cutoff of 4.4 mg/kg/day by IBW (about 300 mg CBA per day for a patient with an IBW of 70 kg) to be most predictive of improvements in global cure rates. Another unique aspect of the current study is the incorporation of dose adjustments and adjudication of doses based on renal function, which were not discussed in the previous studies (11,12). Recent advances in the understanding of colistin elimination provide further insights into the need for renal adjustments (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to those suggested by the manufacturers, the regimens in recent studies support the administration of a loading dose and of higher doses of CMS in order to achieve adequate colistin concentrations leading to a better therapeutic effect (21,41,47). The dosing regimen currently recommended by the recent literature (for patients with good renal function) is a loading dose of 4.5 MU of CMS followed by maintenance doses of 4.5 MU twice daily (48)(49)(50).…”
Section: Use Of Colistin In Human and Veterinary Medicine Use In Humamentioning
confidence: 99%
“…Despite these recent advancements in our understanding of the PK and PD of polymyxins, few studies have reported clinical outcomes in patients receiving these agents, and most evaluated colistin (12)(13)(14). Due to differences in PK and PD parameters, these results may not apply to polymyxin B (15).…”
mentioning
confidence: 99%